Crystal engineering principles: fluoroquinolone salts - Dandela, Rambabu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: ciprofloxacin; Fluoroquinolone; norfloxacin

Pharmaceutical solids in crystal engineering - Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Supramolecular synthon

Supramolecular synthon hierarchy in bumetanide cocrystals - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Novel cocrystals of sulfonamide drug Bumetanide with carboxamides are developed based on supramolecular synthons approach

Crystal engineering of a zwitterionic drug to neutral cocrystals: a general solution for floxacins - Gunnam, Anilkumar; Suresh, Kuthuru; Ganduri, Ramesh; Nangia, Ashwini (Chemical Communications, 2016)
The transformation of zwitterionic Sparfloxacin (SPX) to the neutral form is achieved by cocrystallization. Neutral forms of drugs are important for higher membrane permeability, while zwitterions are more soluble in water. The twin advantages of higher solubility/dissolution rate and good stability of neutral SPX are achieved in a molecular cocrystal compared to its zwitterionic SPX hydrate. The amine-phenol supra-molecular synthon drives cocrystal formation, with the paraben ester acting as a "proton migrator'' for the ionic to neutral transformation.

Pharmaceutical cocrystals: walking the talk - Bolla, Geetha; Nangia, Ashwini (Chemical Communications, 2016)
Pharmaceutical cocrystals belong to a sub-class of cocrystals wherein one of the components is a drug molecule (or an active pharmaceutical ingredient, API) and the second is a benign food or drug grade additive (generally regarded as safe, GRAS). The two components are hydrogen-bonded in a fixed stoichiometric ratio in the crystal lattice. In the past decade, pharmaceutical cocrystals have demonstrated significant promise in their ability to modify the physicochemical and pharmacokinetic properties of drug substances, such as the solubility and dissolution rate, bioavailability, particle morphology and size, tableting and compaction, melting point, physical form, biochemical and hydration stability, and permeability. In this feature review, we highlight some prominent examples of drug cocrystals which exhibit variable hardness/softness and elasticity/plasticity depending on coformer selection, improvement of solubility and permeability in the same cocrystal, increase of the melting point for solid formulation, enhanced color performance, photostability and hydration stability, and a longer half-life. Cocrystals of flavanoids and polyphenols can make improved pharmaceuticals and also extend to the larger class of nutraceuticals. The application of crystal engineering to assemble ternary cocrystals expands this field to drug-drug cocrystals which may be useful in multi-drug resistance, mitigating side effects of drugs, or attenuating/enhancing drug action synergistically by rational selection. The advent of new techniques for structural characterization beyond the standard X-ray diffraction will provide a better understanding of drug phases which are at the borderline of crystalline-amorphous nature and even newer opportunities in the future.

Syringic acid: structural elucidation and co-crystallization - Thipparaboina, Rajesh; Mittapalli, Sudhir; Thatikonda, Sowjanya; Nangia, Ashwini; Naidu, V. G. M.; Shastri, Nalini R. (Crystal Growth & Design, 2016)
Syringic acid (SYRA) is a potential antioxidant used in traditional Chinese medicine and is an emerging nutraceutical. Current reports claim its potential anti-angiogenic, anti-glycating, anti-hyperglycaemic, neuroprotective, and memory-enhancing properties in various animal models. To date, SYRA crystal structure has not been elucidated, and no crystal engineering studies have been reported. This study reports the crystal structure of SYRA for the first time along with its nicotinamide (SNCT-E) and urea (SU-EA-M) co-crystals. All forms were successfully characterized using single crystal X-ray diffraction (XRD), powder XRD, and differential scanning calorimetry. Single crystal analysis revealed that SYRA crystallized in the C2/c space group, whereas SNCT-E (2:1) and SU-EA-M (1:2) crystallized in the P21/n and Cmca space group, respectively. Novel co-crystals have shown improved solubility, modified dissolution profiles, and improved flow and compressibility. Cytotoxic effects were explored in DU145 prostate cancer cell lines for the first time, and significant enhancement in cytotoxicity by the co-crystals was observed compared to plain components. A two-fold increase in % cytotoxicity of SNCT-E was observed when compared to the corresponding physical mixture. These studies shed light on potential utility of SYRA as a coformer for various pharmaceutical applications to design synergistic and organ-protective co-crystals.

Tracing the architecture of caffeic acid phenethyl ester cocrystals: studies on crystal structure, solubility, and bioavailability implications - Ketkar, Sameer; Pagire, Sudhir K.; Goud, N. Rajesh; Mahadik, Kakasaheb R.; Nangia, Ashwini; Paradkar, Anant (Crystal Growth & Design, 2016)
Caffeic acid phenethyl ester (CAPE) is a polyphenolic active compound present in popular apiproduct, "propolis", obtained from beehives, Though it has broad therapeutic capability, the bioavailability of CAPE is limited due to poor solubility. In this study, we report novel cocrystals of CAPE engineered using coformers such as caffeine (CAP), isonicotinamide (INIC), and nicotinamide (NIC) with enhanced solubility and bioavailability of CAPE. The cocrystals were prepared by microwave-assisted cocrystallization and characterized using PXRD, DSC, and Raman spectroscopy. PXRD and DSC confirm the successful formation and phase purity of CAPE-CAF, CAPE-INIC, and CAPE-NIC cocrystals. Raman spectra of CAPE cocrystals complement these results in confirming the formation of novel crystalline phases. CAPE-NIC cocrystal was further subjected X-ray crystallography to understand its molecular arrangement and hydrogen bonding in the crystal structure. The CAPE-NIC cocrystal structure is found to be stabilized by a rare 1,2-benzenediol-amide heterosynthon. Cocrystallization of CAPE with NIC improved its aqueous solubility and pharmacokinetic profile, thereby demonstrating a 2.76-fold escalation in bioavailability.

Use of the term "crystal engineering" in the regulatory and patent literature of pharmaceutical solid forms. some comments - Desiraju, Gautam R.; Nangia, Ashwini (Crystal Growth & Design, 2016)

Acemetacin cocrystal structures by powder X-ray diffraction - Bolla, Geetha; Chernyshev, Vladimir; Nangia, Ashwini (Iucrj, 2017)
Cocrystals of acemetacin drug (ACM) with nicotinamide (NAM), p-aminobenzoic acid (PABA), valerolactam (VLM) and 2-pyridone (2HP) were prepared by melt crystallization and their X-ray crystal structures determined by high-resolution powder X-ray diffraction. The powerful technique of structure determination from powder data (SDPD) provided details of molecular packing and hydrogen bonding in pharmaceutical cocrystals of acemetacin. ACM-NAM occurs in anhydrate and hydrate forms, whereas the other structures crystallized in a single crystalline form. The carboxylic acid group of ACM forms theacid-amide dimer three-point synthon R-3(2)(9) R-2(2)(8) R-3(2)(9) with three different syn amides (VLM, 2HP and caprolactam). The conformations of the ACM molecule observed in the crystal structures differ mainly in the mutual orientation of chlorobenzene fragment and the neighboring methyl group, being anti (type I) or syn (type II). ACM hydrate, ACM-NAM, ACM-NAM-hydrate and the piperazine salt of ACM exhibit the type I conformation, whereas ACM polymorphs and other cocrystals adopt the ACM type II conformation. Hydrogen-bond interactions in all the crystal structures were quantified by calculating their molecular electrostatic potential (MEP) surfaces. Hirshfeld surface analysis of the cocrystal surfaces shows that about 50% of the contribution is due to a combination of strong and weak O center dot center dot center dot H, N center dot center dot center dot H, Cl center dot center dot center dot H and C center dot center dot center dot H interactions. The physicochemical properties of these cocrystals are under study.

Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism

Polymorphism, isostructurality and physicochemical properties of glibenclamide salts - Suresh, Kuthuru; Khandavilli, U. B. Rao; Gunnam, Anilkumar; Nangia, Ashwini (CrystEngComm, 2017)
Novel salts of glibenclamide (GBA), namely glibenclamide-sodium (GBA-Na), glibenclamide-potassium (GBA-K) and glibenclamide-ammonium (GBA-NH4) were crystallized under different conditions to obtain their polymorphs, and their aqueous solubility and hydration stability studies are reported. The GBA-Na salt is dimorphic (forms I and II)and also exists as hydrate GBA-Na-H2O (form III). The GBA-K salt exists in anhydrous and hydrate forms (GBA-K, forms I and II). Crystal structure analysis of GBA-Na forms I and II showed differences in geometry of the central metal atom and ligand orientation. This kind of polymorphism of sulfonyl urea salts appears to be novel in the Cambridge Structural Database (CSD). The iso-structurality of GBA-Na form I with GBA-NH4 and GBA-K form I salts is discussed. The potassium salts of GBA exhibited higher solubility compared to pure GBA. Specifically GBA-K salt forms I and II showed higher solubility by 77 fold in the water and 33 fold in phosphate buffer (pH 7) compared to the other salts. Dynamic vapor sorption (DVS) showed reversible water sorption without hysteresis for all salts, except for GBA-K form II which transformed to form I after a sorption and desorption cycle as confirmed by PXRD.

Supramolecular synthons in bumetanide cocrystals and ternary products - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Crystal Growth & Design, 2017)
A novel design strategy for cocrystals of the diuretic sulfonamide drug bumetanide (BUM) with carboxamides is reported based on reliable supramolecular synthons. Binary cocrystals of BUM with pyridine carboxamides, pyridones, and cytosine were obtained by solvent assisted grinding followed by solution crystallization. All cocrystal structures exhibit hydrogen bonding of the coformer with the carboxylic acid group of BUM via heterosynthons which replace the acid homodimer in the drug crystal structure. Pyridones are inserted as N-H center dot center dot center dot O dimers which are in turn bonded to the acid group of BUM, while the pyridine amide coformers interact via the acid amide heterosynthon. Cocrystal polymorphs were obtained for bumetanide isonicotinamide cocrystal structure with the sulfonamide pyridine and sulfonamide acid synthons. Careful crystal packing analysis of BUM structure and nine new binary adducts gave an idea for the design ternary cocrystals, and subsequently four new ternary crystalline products were crystallized. Whereas the binary cocrystal structures were confirmed by single crystal diffraction, the ternary combinations were chatacterized by their unique powder X-ray diffraction patterns as well as by thermal and spectroscopic techniques.

Thermomechanical effect in molecular crystals: the role of halogen-bonding interactions - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nanubolu, Jagadeesh Babu; Nangia, Ashwini (IUCRJ, 2017)
The design and synthesis of mechanically responsive materials is interesting because they are potential candidates to convert thermal energy into mechanical work. Reported in this paper are thermosalient effects in a series of halogen derivatives of salinazids. The chloro derivative, with higher electronegativity and a weaker inter-halogen bond strength (Cl center dot center dot center dot Cl) exhibits an excellent thermal response, whereas the response is weaker in the iodo derivative with stronger I center dot center dot center dot I halogen bonding. 3,5-Dichlorosalinazid (Compound-A) exists in three polymorphic forms, two room-temperature polymorphs (Forms I and II) and one high-temperature modification (Form III). The transformation of Form I to Form III upon heating at 328-333 K is a reversible thermosalient transition, whereas the transformation of Form II to Form III is irreversible and nonthermosalient. 3,5-Dibromo- (Compound-B) and 3-bromo-5-chloro(Compound-C) salinazid are both dimorphic: the Form I to Form II transition in Compound-B is irreversible, whereas Compound-C shows a reversible thermosalient effect (362-365 K). In the case of 3,5-diiodosalinazid (CompoundD) and 3,5-difluorosalinazid (Compound-E), no phase transitions or thermal effects were observed. The thermosalient behaviour of these halosalinazid molecular crystals is understood from the anisotropy in the cell parameters (an increase in the a axis and a decrease in the b and c axes upon heating) and the sudden release of accumulated strain during the phase transition. The dihalogen salinazid derivatives (chlorine to iodine) show a decrease in thermal effects with an increase in halogen-bond strength. Interestingly, Compound-B shows solid-state photochromism in its polymorphs along with the thermosalient effect, wherein Form I is cyan and Form II is light orange.

Curcumin: pharmaceutical solids as a platform to improve solubility and bioavailability - Suresh, Kuthuru; Nangia, Ashwini (Crystengcomm, 2018)
Curcumin (CUR) is the prime curcuminoid in the Indian dietary spice turmeric, Curcuma longa, a plant of the Zingiberaceae family. CUR has promising and diverse therapeutic benefits, such as antioxidant, anti-inflammatory, antitumor, anti-hyperglycemic, antimalarial, antibacterial, and antiviral activity, including anti-Alzheimer's disease. However, CUR is yet to reach the status of a therapeutic drug candidate mainly because a standard solid dosage of curcumin suffers from poor oral bioavailability (0.05 g mL(-1), less than 1%). The reasons behind its low bioavailability include poor solubility (<8 g mL(-1) in water), low permeability and absorption, and rapid metabolism (short elimination half-life of <2 h). A successful CUR therapy requires an appropriate formulation system that will enhance the bioavailability and offer greater therapeutic efficacy. This review covers a comprehensive description of the CUR pharmaceutical solids, such as polymorphs, cocrystals, eutectics, and coamorphous solid-state forms with aim to determine ways to improve its physicochemical properties, including dissolution rate, solubility, physicochemical stability, mechanical strength, compressibility for tablet formation, and oral bioavailability. The cumulative publications in the past decade have forecast a bright future for development of an oral drug formulation of curcumin.

Curcumin-artemisinin coamorphous solid: Xenograft model preclinical study - Mannava, M. K. Chaitanya; Suresh, Kuthuru; Bommaka, Manish Kumar; Konga, Durga Bhavani; Nangia, Ashwini (Pharmaceutics, 2018)
Curcumin is a natural compound present in Indian spice turmeric. It has diverse pharmacological action but low oral solubility and bioavailability continue to limit its use as a drug. With the aim of improving the bioavailability of Curcumin (CUR), we evaluated Curcumin-Pyrogallol (CUR-PYR) cocrystal and Curcumin-Artemisinin (CUR-ART) coamorphous solid. Both of these solid forms exhibited superior dissolution and pharmacokinetic behavior compared to pure CUR, which is practically insoluble in water. CUR-ART coamorphous solid showed two fold higher bioavailability than CUR-PYR cocrystal (at 200 mg/kg oral dose). Moreover, in simulated gastric and intestinal fluids (SGF and SIF), CUR-ART is stable up to 3 and 12 h, respectively. In addition, CUR-PYR and CUR-ART showed no adverse effects in toxicology studies (10 times higher dose at 2000 mg/kg). CUR-ART showed higher therapeutic effect and inhibited approximately 62% of tumor growth at 100 mg/kg oral dosage of CUR in xenograft models, which is equal to the positive control drug, doxorubicin (2 mg/kg) by i.v. administration.

Entacapone: improving aqueous solubility, diffusion permeability, and cocrystal stability with theophylline - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Suresh, Kuthuru; Gunnam, Anilkumar; Nangia, Ashwini (Crystal Growth & Design, 2018)
Cocrystallization is a well-established technique to improve the solubility, bioavailability, and stability of active pharmaceutical ingredients (APIs) but permeability and diffusion rate control via cocrystals is relatively less well studied, and the exact role of coformers in influencing the diffusion rate of drug cocrystals is still not fully understood. The aqueous solubility and permeability diffusion of Entacapone, ETP, a Biopharmaceutical Classification System (BCS) Class IV drug of low solubility and low permeability, with Generally Regarded as Safe (GRAS) coformers has been studied. Fixed stoichiometry cocrystals of ETP with acetamide (ACT, 1:1), nicotinamide (NAM, 1:1), isonicotinamide (INAM, 1:1), pyrazinamide (PYZ, 1:1), and isoniazid (INZ), 1:1) were prepared by solvent-assisted grinding. Theophylline (THP) resulted in a cocrystal hydrate (ETP-THP-FIYD 1:1:1). The cocrystals were structurally characterized by single crystal and powder X-ray diffraction, DSC and TGA thermal measurements, and IR and NMR spectroscopy. Solubility and dissolution rate showed that there is a correlation between cocrystal stability and solubility governed by the heteromeric N-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O hydrogen bonds and conformational changes of ETP in cocrystal structures. ETP-THP-HYD and ETP-PYZ exhibit faster dissolution rate and high solubility and they are stable in phosphate buffer medium compared to the other cocrystals which dissociate partially during solubility experiments. Diffusion rates in a Franz cell showed that the stable and high solubility ETP-THP-HYD cocrystal has good permeability. Given that stability, solubility, and permeability are in general inversely correlated, the entacapone-theophylline hydrate cocrystal is a unique example of the thermodynamically stable cocrystal exhibiting high solubility and high permeability.

Novel pharmaceutical salts of albendazole - Bolla, Geetha; Nangia, Ashwini (Crystengcomm, 2018)
Albendazole (ABZ) is a class II safe and effective antihelmintic drug in the benzimidazole group according to the BCS (Biopharmaceutics Classification System) with low solubility (9 mg L-1) and high permeability (log P 2.54). Novel salts and salt hydrates of ABZ are reported with benzene and p-toluene sulfonic acid (BSA, PTSA), as well as carboxylic acids such as oxalic acid (OA), maleic acid (MLE), L-tartaric acid (LTA), 2,6-dihydroxybenzoic acid (2,6-DHBA), and 2,4,6-trihydroxybenzoic acid (2,4,6-THBA). The products ABZ-BSA, ABZ-BSA-H, ABZ-PTSA, ABZ-PTSA-H, ABZ-OA-H and ABZ-2,6-DHBA were confirmed by single crystal X-ray diffraction. In the hydrate structures (designated as -H), the water molecule acts as a bridge in the hydrogen bonding network. The salt formation of ABZ-MLE, ABZ-LTA, and ABZ-2,4,6-THBA was confirmed by N-15 ss-NMR based on the chemical shift change of ca. 50 ppm. The sulfonate salt hydrates exhibit 2D isostructurality, and position disorder in the thiopropyl group in the drug crystal structure was not observed in the salts. Crystal lattice energies were calculated for the MLE, LTA, and 2,4,6-THBA complexes of ABZ to confirm the molecular salt formation. The cocrystals of ABZ with the hydroxybenzene carboxylic acids are novel salts in the benzimidazole drugs class.

Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Salts and salt cocrystals of the antibacterial drug pefloxacin - Gunnam, Anilkumar; Suresh, Kuthuru; Nangia, Ashwini (Crystal Growth & Design, 2018)
Pefloxacin (PEF) is an amphoteric, antibacterial drug which exists as a neutral molecule in the crystal structure stabilized by C-H center dot center dot center dot O and C-H center dot center dot center dot F interactions. The design of multicomponent solids using crystal engineering was undertaken in a cocrystal/salt screen of PEF with generally recognized as safe (GRAS) dicarboxylic acids to improve the solubility and phase stability of the drug. Ten multicomponent forms, namely, five salts, two salt hydrates, and three salt cocrystals, were prepared by liquid-assisted grinding followed by crystallization. In some cases, salt and salt cocrystals were obtained concomitantly during solution evaporative crystallization. Single crystal X-ray diffraction showed that the structures are stabilized by N+-H center dot center dot center dot O-, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot F, and pi-pi stacking interactions. The bulk phase purity of multicomponent forms was characterized by powder X-ray diffraction, spectroscopy, and thermal techniques. The salt/salt cocrystal forms exhibit a faster dissolution rate and higher solubility compared to pure PEF in pH 1.2 (acidic, like gastric environment) and pH 7 phosphate buffer media (neutral, like intestinal passage). Specifically the PEF+-SA(-) salt (SA = succinic acid) showed remarkably high solubility, dissolution rate, and stability compared to the other multicomponent forms and PEF neutral form. The drug formulation compatible pefloxacin succinate is a promising soluble and stable PEF salt.

Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

Cocrystals, salts, and supramolecular gels of nonsteroidal anti inflammatory drug niflumic acid - Mittapalli, Sudhir; Mannava, M. K. Chaitanya; Sahoo, Rasmita; Nangia, Ashwini (Crystal Growth & Design, 2019)
Niflumic acid (NFA) is a nonsteroidal anti-inflammatory drug (NSAID) classified under the BCS (Biopharmaceutical Classification System) Class II category of poor aqueous solubility and high permeability. In an attempt to improve the physicochemical properties of NFA, particularly solubility and dissolution rate by cocrystallization and salt formation, cocrystals of NFA were prepared with caprolactam (CPR, 1:1) and 2-hydroxy pyridine (2HP, 1:1) as well as salts with piperazine (PIP, 1:0.5), benzenesulfonic acid (BSA, 1:1), benzyl amine (BZA, 1:1 and 2:2), and tyramine (TYA, 1:1). The new solid forms were characterized by powder X-ray diffraction, infrared spectroscopy, and differential scanning calorimetry and confirmed by single crystal X-ray diffraction. In the cocrystals NFA CPR and NFA-2HP, the cyclic amide of the coformer forms a dimer synthon through N-H center dot center dot center dot O hydrogen bonds and such dimers extend through O-H center dot center dot center dot O hydrogen bonds. In piperazine, benzyl amine, and tyramine salts, proton transfer occurs from the NFA to the basic nitrogen of the coformer, and in NFA BSA salt, the proton is transferred from benzenesulfonic acid to the pyridine nitrogen of NFA. In addition to the above salts and cocrystals, supramolecular gels of NFA-PIP and NFA-BZA salts are reported, which were obtained from nitrobenzene, methyl salicylate, menthol, and mesitylene solvents. These gels were studied by rheology. Solubility and dissolution rate of the novel solid forms (NFA CPR, NFA PIP, NFA BSA, and NFA TYA) in 20% EtOH water showed the best behavior for NFA-TYA salt with improvement of 42-and 54-times in solubility and dissolution rate compared to the reference drug. The remaining solids such as NFA-PIP, NFA-BSA salts, and NFA-CPR cocrystal exhibited improvement of 39-, 18-, 1.4-times in solubility and 7.8-, 10-, 2-times for dissolution rate.

Crystalline acylhydrazone photoswitches with multiple mechanical responses - Gupta, Poonam; Panda, Tamas; Allu, Suryanarayana; Borah, Silpisikha; Baishya, Anamika; Gunnam, Anilkumar; Nangia, Ashwini; Naumov, Pance; Nath, Naba K. (Crystal Growth & Design, 2019)
The advancement of our understanding of stimuli responsive molecular crystals has led to the realization that they hold great yet unexplored potential as adaptive materials. Although molecular crystals that exhibit a single mechanical response to a single input stimulus are now abundant, crystals that are capable of response to multiple stimuli are rather scarce. Here we report two photoswitchable acylhydrazone derivatives, Ac-1 and Ac-2, which respond to light as well as to mechanical force. Upon application of localized mechanical stress, the anhydrous (Ac-1a) and monohydrate (Ac-1h) crystals of Ac-1 undergo plastic shearing deformation and bending, whereas monohydrate crystals of Ac-2 undergo elastic deformation. When they are exposed to UV light, crystals of Ac-1h and Ac-2 undergo photoinduced bending; on the other hand, crystals of Ac-1a and thicker crystals of Ac-2 exhibit photosalient effect (light-induced leaping). It is demonstrated that the synergistic action of multiple stimuli (UV light and force) elicits enhanced mechanical response, and this strategy could be employed in the future to increase the efficacy of single crystal actuators.

Electron crystallography - Blake, Alexander J.; de Boissieu, Marc; Nangia, Ashwini (IUCRJ, 2019)

Quantification of niclosamide polymorphic forms - a comparative study by Raman, NIR and MIR using chemometric techniques - Bhavana, Valmala; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Nangia, Ashwini; Shastri, Nalini R. (Talanta, 2019)
Niclosamide, an anthelmintic drug recently repurposed for its activity against cancer, crystallizes into three solvated forms, two monohydrates (NHa, NHb) and one anhydrous (NAn) form. NAn is sensitive to pseudopolymorphic transformations that affect its dissolution and consequently, its bioavailability. NAn exhibits a polymorphic conversion to metastable monohydrate (NHa) form during high-energy milling in presence of poorly soluble solvents like water. It is hence very important to quantify polymorphic conversion from NAn to NHa, as water is a commonly used solvent during various processing like ball milling and wet granulation. This main objective of the study was to examine the feasibility of Raman, NIR and MIR spectroscopic techniques for identification and quantification of polymorphic forms of niclosamide in binary mixtures and multicomponent mixtures. Calibration models were developed and validated by vibrational spectroscopic techniques in binary mixtures of NAn and NHa and in multicomponent mixtures by chemometric techniques. These techniques were further used to identify and quantify NHa during ball milling, granulation and in presence of other polymorphic forms of niclosamide. Identification and quantification of pseudopolymorphs in binary and multicomponent mixtures with an acceptable recovery of 100.13-102.99% for Raman and 100.07-101.28% for NIR with low % RSD of 2.38-3.12 for both techniques were obtained. The % NHa determined during ball milling and granulation was similar by NIR and Raman. Raman spectroscopy however showed a greater advantage over other techniques in determining the NHa in presence of NHb due to significant difference in the spectral region of hydrates, when compared to NIR and MIR.
Keywords: Ball milling; Granulation; MSC; PLS; Polymorphic conversion; spectroscopy

Role of hydrogen bonding in cocrystals and coamorphous solids: indapamide as a case study - Allu, Suryanarayana; Suresh, Kuthuru; Bolla, Geetha; Mannava, M. K. Chaitanya; Nangia, Ashwini (Crystengcomm, 2019)
The stronger sulfonamide-pyridine (SO2NH2 center dot center dot center dot N-Py) and sulfonamide-carboxamide (SO2NH2 center dot center dot center dot O = C-NH) hydrogen bonds direct the formation of cocrystals, while the weaker sulfonamide-amine (SO2NH2 center dot center dot center dot N-H) hydrogen bond results in coamorphous products. IDP-PIP and IDP-ARG coamorphous solids exhibit remarkable stability under accelerated conditions.

Supramolecular synthon hierarchy in sulfonamide cocrystals with syn-amides and N-oxides - Bolla, Geetha; Nangia, Ashwini (IUCRJ, 2019)
Sulfonamide drugs are well known antibacterial and antimicrobial molecules for pharmaceutical development. Building a library of suitable supramolecular synthons for the sulfonamide functional group and understanding their crystal structures with partner coformer molecules continues to be a challenge in crystal engineering. Although a few sulfonamide cocrystals with amides and N-oxides have been reported, the body of work on sulfonamide synthons is limited compared with those that have carboxylic acids and carboxamides. To address this structural gap, the present work is primarily focused on sulfonamide-lactam and sulfonamide-syn-amide synthons with drugs such as celecoxib, hydrochlorothiazide and furosemide. Furthermore, the electrostatic potential of previously reported cocrystals has been recalculated to show that the negative electrostatic potential on the lactam and syn-amide O atom is higher compared with the charge on carboxamide and pyridine N-oxide O atoms. The potential of sulfonamide molecules to form cocrystals with syn-amides and lactams are evaluated in terms of the electrostatic potential energy for the designed supramolecular synthons.
Keywords: cocrystals; crystal engineering; sulfonamides; supramolecular synthons; syn-amides

Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.

Resolving salt-cocrystal conundrum in multicomponent crystals by using X-ray quantum crystallography - Sudheendranath, Athul; Tothadi, Srinu; Pradhan, Amit Kumar; Prajapati, Aditya Kumar; Nangia, Ashwini; Thomas, Sajesh P. (Journal of Physical Chemistry C, 2025)
The structural identity of multicomponent crystals as a salt or cocrystal is dictated by the proton transfer state between the molecular components. In pharmaceutical drugs, solid-state forms such as salts or cocrystals can have significantly distinct stability, dissolution, and solubility profiles. The accurate location of proton positions is a formidable task using conventional X-ray crystallography, as the atomic scattering factors are based on spherical electron density models. Herein, we demonstrate that the X-ray quantum crystallographic (QCr) technique of Hirshfeld Atom Refinement (HAR), based on aspherical atomic scattering factors, can be effectively employed to resolve this riddle. Our HAR models accurately located the proton positions, thus distinguishing salts, cocrystals, and continuum crystal structures, which are substantiated by the N 1s binding energies from X-ray photoelectron spectroscopy (XPS) corresponding to the base components in a series of crystals. The QCr models reveal the subtle features of electron localization and bonding around the double-well potential in the intermolecular proton-transfer regions in these crystals.